TatD DNases Contribute to Biofilm Formation and Virulence in Trueperella pyogenes - Zhang, Zehui; Liang, Yinfeng; Yu, Lihui; Chen, Menghan; Guo, Yuru; Kang, Zhiruo; Qu, Chenghu; Tian, Chunlian; Zhang, Dexian; Liu, Mingchun (Frontiers in Microbiology, 2021)
TatD DNases are conserved proteins in a variety of organisms and are considered potential virulence factors in Plasmodium falciparum and Streptococcus pneumoniae. However, the function of TatD DNases has not yet been determined in Trueperella pyogenes, which causes various infections in animals and leads to economic losses. In this study, we describe the roles of TatD DNases in T. pyogenes (TpTatDs). A bioinformatics analysis was performed to investigate the sequence characteristics of TpTatDs, and then the ability of recombinant TatD proteins to hydrolyze DNA was determined in the presence of divalent cations. Moreover, we constructed tatD-deficient mutants. The biofilms formed by the wild-type and mutant strains were observed under a microscope. The mortality and bacterial load in the spleen of mice infected with the wild-type strain and tatD-deficient mutants were determined to obtain insights into the role of TatDs in the virulence of T. pyogenes. Two TatD DNases were identified in T. pyogenes. They were Mg2+-dependent DNases and exhibited DNA endonuclease activity. Compared with those formed by the parental strain, biofilms formed by mutants showed a significantly reduced thickness and biomass. Moreover, mutants produced a lower bacterial load in the spleen of mice and compromised virulence. Our data indicated that TatD DNases in T. pyogenes are involved in biofilm formation and required for virulence during infections.